2022
DOI: 10.1097/ta.0000000000003707
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of weight-based enoxaparin dosing for venous thromboembolism prophylaxis in trauma patients: A systematic review and meta-analysis

Abstract: BACKGROUND:Trauma patients are at high risk of developing venous thromboembolism (VTE), and standard dosing enoxaparin regimens may be inadequate for prophylaxis. This meta-analysis was performed to clarify the efficacy of alternative dosing regimens for VTE prophylaxis in this high-risk group. The objective of this systematic review was to review the evidence regarding weight-based dosing of enoxaparin for VTE prophylaxis in trauma patients. METHODS:A systematic database search was undertaken for studies comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…31 A meta-analysis found that weight-based dosing of enoxaparin for VTE prophylaxis was associated with increased odds of anti-Xa levels at goal, with no difference in bleeding or VTE events. 22 Most of the hospitals in our study used similar dosing strategies based upon weight, BMI, or a hybrid of both. In our study, 61% of initial peak anti-Xa levels were within our target range of 0.2-0.4 units/mL, with the BMI-based dosing group having the highest rate of suboptimal anti-Xa levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…31 A meta-analysis found that weight-based dosing of enoxaparin for VTE prophylaxis was associated with increased odds of anti-Xa levels at goal, with no difference in bleeding or VTE events. 22 Most of the hospitals in our study used similar dosing strategies based upon weight, BMI, or a hybrid of both. In our study, 61% of initial peak anti-Xa levels were within our target range of 0.2-0.4 units/mL, with the BMI-based dosing group having the highest rate of suboptimal anti-Xa levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a study describing implementation of an anti‐Xa monitoring protocol, 75% of patients had initial anti‐Xa level at goal using enoxaparin 30 mg twice daily in patients 50–100 kg and with BMI <40 kg/m 2 , or 40 mg twice daily in patients ≥100 kg or with BMI ≥40 kg/m 2 31 . A meta‐analysis found that weight‐based dosing of enoxaparin for VTE prophylaxis was associated with increased odds of anti‐Xa levels at goal, with no difference in bleeding or VTE events 22 . Most of the hospitals in our study used similar dosing strategies based upon weight, BMI, or a hybrid of both.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with a xed dosage, a weight-based dosage may be more effective in reaching the expected anti-Xa level (9). Additionally, weight has been proven to be a key predictor of anti-Xa level (10). Thus, our study is designed to administer weight-based dosage of LMWH, instead of xed dosage as usual, to achieve better effect in preventing VTE.…”
Section: Introductionmentioning
confidence: 99%